Pharmacokinetics of Cannabis and Its Derivatives in Animals and Humans During Pregnancy and Breastfeeding - Monfort, Anaëlle; Ferreira, Ema; Leclair, Grégoire; Lodygensky, Gregory Anton (Frontiers in Pharmacology, 2022)
Cannabis is one of the drugs most widely used during pregnancy and lactation. With the recent legalization of cannabis in many countries, health professionals are increasingly exposed to pregnant and breastfeeding women who are consuming cannabis on a regular basis as a solution for depression, anxiety, nausea, and pain. Cannabis consumption during pregnancy can induce negative birth outcomes such as reduced birth weight and increased risk of prematurity and admission to the neonatal intensive care unit. Yet, limited information is available regarding the pharmacokinetics of cannabis in the fetus and newborn exposed during pregnancy and lactation. Indeed, the official recommendations regarding the use of cannabis during these two critical development periods lack robust pharmacokinetics data and make it difficult for health professionals to guide their patients. Many clinical studies are currently evaluating the effects of cannabis on the brain development and base their groups mostly on questionnaires. These studies should be associated with pharmacokinetics studies to assess correlations between the infant brain development and the exposure to cannabis during pregnancy and breastfeeding. Our project aims to review the available data on the pharmacokinetics of cannabinoids in adults, neonates, and animals. If the available literature is abundant in adult humans and animals, there is still a lack of published data on the exposure of pregnant and lactating women and neonates. However, some of the published information causes concerns on the exposure and the potential effects of cannabis on fetuses and neonates. The safety of cannabis use for non-medical purpose during pregnancy and breastfeeding needs to be further characterized with proper pharmacokinetic studies in humans feasible in regions where cannabis has been legalized. Given the available data, significant transfer occurs to the fetus and the breastfed newborn with a theoretical risk of accumulation of products known to be biologically active.